ENCYCLOPEDIA OF BUGS - Twist, Clint (Essex, United Kingdom : Miles Kelly Publishing Ltd., 2018)
This amazing book presents a detailed look at the world of creepy-crawlies including spiders, beetles, butterflies, grasshoppers and bees. Accessible bulleted facts, photographs, realistic artwork and detailed diagrams throughout make this series a fantastic resource for school projects or homework.
Includes index
Keywords: Insects -- Encyclopedias, Juvenile